(untitled) (NEW: Emerging scholars in Australian Indigenous Studies, 2020)
Through colonial eyes, Aboriginal and Torres Strait Islander people are seen as subjects void of agency. They have been treated by the Australian polity as though they are in great need of saving. This paper explores the ways in which well-intended policies and initiatives implemented by successive governments have failed to recognise and support Indigenous Australians as functioning sovereign beings.